Comparing the kinetic activation energy of the oxygen evolution and reduction reactions. (10th August 2018) - Suermann, Michel; Schmidt, Thomas J.; Büchi, Felix N.
Abstract: The reduction of the activation or kinetic overpotential for the oxygen evolution and reduction reactions (OER/ORR) is of central significance to optimize conversion efficiency of polymer electrolyte water electrolysis and fuel cells (PEWE/PEFC). In both cases increasing temperature seems to be an option. In this work, similarities and differences of the temperature-dependence of the kinetic overpotential of the oxygen evolution and reduction reactions are investigated. While both overpotentials decrease with temperature, only in PEWE a significant cell performance gain is obtained at relevant current densities due to the decreasing reversible thermodynamic cell voltage with temperature. Furthermore, for both reactions, the corresponding activation energies at constant overpotentials and constant cell voltages are determined according to the Butler-Volmer equation and transition state theory. At constant overpotentials a similar decrease in the activation energy from equilibrium conditions (approx. 67 kJ/mol) to an overpotential of about 0.3 V (approx. 40 kJ/mol) is observed and considered as a coincidence. That is, the activation energy of the supposed rate determining steps behaves similar with increasing the OER/ORR overpotential. Considering the technically important situation of constant cell voltage, the activation energy for PEFC is decreasing more rapidly due to the temperature induced decrease of the reversible thermodynamic cell voltage.